Peningkatan Kompetensi Masyarakat melalui Pelatihan Pemasangan Instalasi Listrik Domestik dan Panel Surya - Oriza Candra; Aswardi Aswardi; Elfizon Elfizon; Syaiful Islami; Nevi Faradina; Citra Dewi; Doni Tri Putra Yanto; Erita Astrid (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Abstract—The potential for solar energy sources is so large that it has not been optimally utilized, as a renewable energy source. The use of solar energy as a generator of electricity is very potential to be developed in West Sumatra Province. We know that the price of electricity obtained from this non-renewable energy is much more expensive in the short term, but it is much more valuable when calculated in the long term, especially from the aspect of environmental protection. The continuity of electrical services can always be fulfilled. It is necessary to combine PLN electricity sources and electricity sourced from solar energy as an alternative so that the reliability of the supply of electrical energy can be maintained. However, the large potential of renewable energy sources has not been able to be utilized optimally by the wider community, due to the limited competence of human resources who are able to utilize this energy. Through community service activities, Padang State University in collaboration with the Budi Utama Youth Assisted Child Orphanage in Lubuk Alung tries to make a contribution to improving Human Resource Competence through empowerment and community training with an integrated and sustainable process. One of the competency improvement activities carried out is training on the skills of installing electricity from PLN sources and solar energy installations. This training activity aims to provide understanding in the planning, design, operation, and maintenance of PLN sources and solar panel installations. The end result of this training is being able to provide education, increase skills, and competencies to participants to improve technical skills.